New Trends in Mechanism and Machine Science Theory and Industrial Applications - Wenger, Philippe; Flores, Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book collects the most recent advances in mechanism science and machine theory with application to engineering. It contains selected peer-reviewed papers of the sixth International Conference on Mechanism Science, held in Nantes, France, 20-23 September 2016, covering topics on mechanism design and synthesis, mechanics of robots, mechanism analysis, parallel manipulators, tensegrity mechanisms, cable mechanisms, control issues in mechanical systems, history of mechanisms, mechanisms for biomechanics and surgery and industrial and nonindustrial applications.
Herder -- Synthesis and optimisation of large stroke flexure hinges, by Martijn Grootens, Ronald Aarts and Dannis Brouwer -- On the grand 4R four-bar based inherently balanced linkage architecture, by Volkert van der Wijk -- Mechanism Analysis 2 -- A Workspace Analysis of 4R Manipulators Via Level-Set Formulation, by Matteo Russo and Marco Ceccarelli -- A constructive method for the approximation of the multiple inverse kinematics solutions of noncuspidal 6 DoF manipulators, by Vassilis Moulianitis, Dimitrios Vogiatzief and Nikos Aspragathos -- Single-loop Foldable 8R Mechanisms with Multiple Modes, by Jieyu Wang, Guochao Bai and Xianwen Kong -- Calibration of TCP-fixed bevel units, by Carsten Teichgräber, Maik Berger and Jörg Müglitz -- Industrial and non-industrial applications 2 -- Mechanism Type Synthesis Approach for Automated Handling and Multiaxial Draping of Reinforcing Textiles, by Jan Brinker, Jascha Paris, Mario Müller, Mathias Hüsing and Burkhard Corves -- Design of a Reciprocal Hip Mechanism with Adjustable Flexion-Extension Coupling Ratios for Prosthetic Applications, by Kuan-Han Chen and Jyh-Jone Lee -- Wind turbine based on antiparallel link mechanism, by Marat Dosaev, Lyubov Klimina and Yury Selyutskiy -- Model and analysis of a novel piezo-electric rotational motor based on deformation wave precession, by Marco Leonesio, Nicola Cau, Giacomo Bianchi and Paolo Bonfiglio -- Estimating characteristics of a contact between sensing element of medical robot and soft tissue, by Anastasya Yakovenko, Irina Goryacheva and Marat Dosaev -- Parallel manipulators 2 -- A coordinate-free dynamical model for cable-driven parallel robots, by Georges Le Vey -- Path Generation Synthesis of Planar Double-Slider Linkages via the Elliptic Coupler Curve, by Gökhan Kiper, Almina Akbalçık and Zehra Betül Şen -- A Controller for Avoiding Dynamic Model Degeneracy of Parallel Robots during Type 2 Singularity Crossing, by Damien Six, Sébastien Briot, Abdelhamid Chriette and Philippe Martinet -- Singularity Analysis of a Wall-mounted Parallel Robot with SCARA Motions, by Guanglei Wu and Shaoping Bai -- Design of a Cable-Driven Four-Bar Mechanism for Arm Rehabilitation, by Talha Eraz and Gökhan Kiper. .
Keywords: Machinery; Control engineering; Robotics; Automation; Manufactures; Machinery and Machine Elements; Control, Robotics, Automation; Machines, Tools, Processes